TINJAUAN FIQH EKONOMI TERHADAP PEMBIAYAAN MODAL KERJA MELALUI MURABAHAH PADA PT BRI SYARIAH - Yoni Hendrawan; Zainuddin (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2021)
This article examines the review of economic fiqh on working capital financing (KUR) through murabahah at PT BRISyariah in terms of contracts and margins. KUR Mikro Syariah uses a murabahah contract on a margin that describes the amount of profit or profit sharing that is determined at the submission of KUR Mikro Syariah. The government provides a margin subsidy, which is the difference between the margin level and the margin burden from KUR Mikro Syariah distributors to KUR Mikro Syariah recipients. How is the implementation of murabahah on working capital financing at PT BRISyariah? and how does the Economic Fiqh review on the implementation of the murabahah? This type of research uses field studies and literature studies. This research method will be analyzed qualitatively, based on the perspective of Economic Jurisprudence, as stated in the Qur'an, Sunnah and fiqh books and / or fatwas. The results of this study found that the implementation of murabahah in working capital financing at PT BRISyariah was carried out by providing murabahah (working capital) financing to customers for purchasing building materials with a margin percentage determined by Islamic banks. This margin is subsidized by the government based on the financing ceiling with a standard margin of 6%. Murabahah financing transactions are only valid once, even though the purchase of goods is made repeatedly. According to the Fiqh of Economics working capital financing (KUR) murabahah at PT. BRISyariah which uses a murabahah contract with the provision of working capital in the form of money is not right. Because, providing working capital in the form of money is more appropriate to use a mudharabah contract.